Copulative verbs in Northern Sotho :a morphosemantic study - Maseko, Julia Refilwe (University of Limpopo, 2005)
The study aimsat finding out thecategorical status of copulatives in Northern Sotho. This will be achieved by examining the morphosemantic features of various copulatives. From a morphological perspective, thestudy focuses on the following types ofcopulative verbs: ke, se, ba, le, na, and COP. The study argues that the foresaid copulatives are not particles but are fully-fledged verbs. As far as the semantic nature of the copulatives is concerned, the study discovered a variety of meanings associated with copulatives, such as the following: the identifying, descriptive,locational and associative. Lastly, the study contends that any research on the copulative in Northern Sotho should be a morphosemantic one, as previous studies focused on one and neglected the other.
Thesis (M. A. (African Languages) --University of Limpopo,2005
Keywords: Copulative verbs; Northern Sotho; Morphosemantic study; Grammar, Comparative and general-Verb.; Grammar, Comparative and general-Verb phrase.; Northern Sotho language-Verb phrase